Волонтерська діяльність в Україні як вид соціальної активності - Болотова, Вікторія Олександрівна; Ляшенко, Наталія Олександрівна; Байдак, Тетяна Михайлівна (Видавництво "Грані", 2018)
У статті описано поняття соціальної активності, критерії для виділення її форм та охарактеризована волонтерська діяльність як один із типів її прояву. З’ясовано основні ознаки, за якими можна відрізнити волонтерську діяльність, визначено ступені залучення до неї. Окремо розглянуті сучасні і традиційні напрямки та форми волонтерства, мотиви участі людей в ньому. Виділено фактори збільшення волонтерської активності в Україні. Наведено дані соціологічного дослідження, в межах якого було виявлено рівень волонтерської активності харків’ян, її основні напрямки і форми. Встановлено, що більшість харків’ян асоціюють волонтерство з наданням допомоги речами, їжею і технікою, тобто вибирають менш затратні за часом і коштами форми, а рівень довіри до волонтерів та інформованість про їх діяльність низькі. Були названі основні причини, якими харків’яни пояснюють відмову від особистої участі у волонтерській діяльності, при цьому виявлено вплив віку, доходу та рівня освіти респондентів на їх значимість. Оцінено вплив особистої участі респондентів у волонтерській діяльності на вибір найбільш актуальних її напрямків і форм, джерел інформації про об’єкти діяльності. Виявлено, в якості основних мотивів участі у волонтерській діяльності, бажання змінити суспільство шляхом вирішення гостросоціальних проблем, прохання близьких допомогти в цій діяльності і співчуття до нужденних, при цьому чоловіки і бідніші активніше бажають змінити суспільство, молодь і домогосподарки проявляють більше співчуття до нужденних. Встановлено сплеск волонтерської активності у зв’язку з військовими подіями на сході країни, який був викликаний співчуттям і прагненням вирішити найгостріші проблеми, але з часом він не переріс в активність по відношенню до типових для волонтерства груп (людей похилого віку, дітей, сиріт, інвалідів), тобто відбулося тимчасове включення в цю діяльність.

The article clarifies the concepts of social activity, volunteer activity, volunteering, volunteer. Volunteer activity is defined as a separate type of social activity. For such a type of social activity, the following features are characteristic: the lack of remuneration in general, voluntariness, the benefit of the group, or society from activities. Volunteering can be organized or unorganized, carried out individually or in a group, public or private organizations. Based on the characteristics of volunteering, volunteers are people who voluntarily, on their own accord, engage in activities that benefit people or the environment and do not require financial compensation. The article describes the results of a sociological study aimed at determining the level of volunteer activity of the inhabitants of Kharkiv. The data obtained during the study allowed us to say that in most cases, volunteering is associated with providing food, things, equipment and housing. To fully develop volunteer practices in society, and to support volunteering by the broad masses, society must trust volunteers and recognize volunteer activities as socially useful. Among Kharkiv people, the level of trust in volunteering is not high, moreover, this level is particularly low among people with secondary education and low income. The main reasons for non-participation in volunteering activities are the conviction of Kharkiv residents that the state, not ordinary citizens, should take care of the poor. Volunteers are more likely to be engaged by respondents with higher education and middle or high levels of prosperity. The most promising areas for volunteering are helping homeless children and orphans, helping the elderly and the disabled, helping the internally displaced people and improving the city. Various forms of volunteering are characteristic of different areas of volunteering. The main forms of assistance to the army and internally displaced people is money and supply providing. Regarding orphans and homeless children, the main forms of assistance are supply help, concerts, festivals and other entertainment activities organizing. The basic forms of assistance to the elderly are assistance in organizing events, assistance with professional counseling, help with supply. The main motive for participation in volunteer activity is the desire to change society by solving acute social problems.
Voluntary activity in Ukraine as a social activity
Keywords: волонтерство; добровільна праця; благодійність; українське суспільство; чинники волонтерської активності; соціальна діяльність; social activity; volunteer movement; volunteer activity; volunteering forms; volunteering directions; volunteer activity factors